2012
DOI: 10.1002/cncr.27877
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal breast cancer documented in large‐format histology sections

Abstract: BACKGROUND:The prognostic significance of molecular phenotype in breast cancer is well established in the literature. Recent studies have demonstrated that subgross lesion distribution (unifocal, multifocal, and diffuse) and disease extent also carry prognostic significance in this disease. However, the correlation of molecular phenotypes with subgross parameters has not yet been investigated in detail. METHODS: In total, 444 consecutive invasive breast cancers that were documented in large-format histology sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Meta-regression showed that there was a positive association between year of publication and the OR for DFS at 5 years (b = 0.279, P \ 0.001). There was also a positive association of small magnitude between the proportion of patients undergoing There was significant inter-study heterogeneity (Cochran's Q P = 0.005, I 2 = 70 %) with four smaller studies [29][30][31][32] showing higher magnitude of effect than two larger studies [8,24]. Exclusion of these four smaller studied led to loss of the association between multifocality and worse DSS (OR 1.15, 95 % CI 0.97-1.35, P = 0.10).…”
Section: Univariable Analyses Of Overall and Disease-free Survivalmentioning
confidence: 93%
“…Meta-regression showed that there was a positive association between year of publication and the OR for DFS at 5 years (b = 0.279, P \ 0.001). There was also a positive association of small magnitude between the proportion of patients undergoing There was significant inter-study heterogeneity (Cochran's Q P = 0.005, I 2 = 70 %) with four smaller studies [29][30][31][32] showing higher magnitude of effect than two larger studies [8,24]. Exclusion of these four smaller studied led to loss of the association between multifocality and worse DSS (OR 1.15, 95 % CI 0.97-1.35, P = 0.10).…”
Section: Univariable Analyses Of Overall and Disease-free Survivalmentioning
confidence: 93%
“…The proposed new classification with ductal origin of the tumour shown on mammogram -such as casting type and architectural distortion -again underscores the independent role of mammographic appearance [17,20]. In addition, the recently proposed histological tumour distribution (including unifocal, multifocal, and diffuse) plays an important role in the prognosis of breast cancer death [21]. Accordingly, the combination of these markers, particularly the triple-negative feature, with mammographic appearance, together with conventional prognostic variables, has the potential to further stratify the risk of breast tumours and to inform individual treatment decisions.…”
Section: Introductionmentioning
confidence: 92%
“…The method has been described in previous studies [21][22][23]. Briefly, before operating, a tumour casting and architectural distortion than among tumours with other types of mammographic appearance.…”
Section: Mammographic Appearance Ihc Markers and Histological Tumoumentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation of the radiologic tumor features with large section histology and long-term patient outcome has demonstrated that the mammographic appearance of breast cancers is a strong prognostic factor [4][5][6][7][8]. Thus, breast imaging, especially mammography, simplifies the histologic complexity of invasive breast cancers, since different histologic subtypes may have identical mammographic presentation.…”
Section: Introductionmentioning
confidence: 99%